Relationship between the oospore dose in the leaf litter above the vineyard ground and primary infections by Plasmopara viticola - Fedele, Giorgia; Maddalena, Giuliana; Furiosi, Margherita; Rossi, Vittorio; Toffolatti, Silvia Laura; Caffi, Tito (Frontiers in Plant Science, 2025)
Plasmopara viticola, the grapevine downy mildew (DM) oomycete, overwinters as oospores in fallen leaves above the vineyard ground. The oospores repeatedly germinate in the following season, causing primary infections on the leaves and clusters. In the present study, the relationship between the numbers of P. viticola oospores in the leaf litter and the dynamics of primary infections on grape leaves were studied for three years to assess whether the assessment of the oospore pool in a vineyard can provide information on the DM pressure. Five leaf litters were prepared by mixing DM-free and -affected leaves in varying proportions in the fall, including 100% DM-free leaves (LL0), 75% DM-free and 25% DM-affected leaves (LL25), 50% DM-free and 50% DM-affected leaves (LL50), 25% DM-free and 75% DM-affected leaves (LL75), and 100% DM-affected leaves (LL100). The leaf litters were overwintered in a vineyard and the oospore pool was quantified in the following season by counting the oospore numbers and assessing P. viticola DNA (Pv DNA) through quantitative polymerase chain reaction (qPCR). There were significant correlations between the prevalence of DM-affected leaves in the leaf litter, the number of oospores (r = 0.969), and the molecular infestation index (MII) calculated based on Pv DNA (r = 0.974). In addition, there were significant correlations between oospore numbers and MII (r = 0.895). Survival analysis showed a significant effect of diseased leaves in the leaf litter on relevant DM onset time during the primary inoculum season. DM lesions on plants increased with an increasing proportion of DM-affected leaves in the leaf litter, with plants above LL100 exhibiting four-fold more lesions than the plants above LL0. Results show that there is a legacy/inheritance factor in a vineyard, which is linked to the oospore pool. This is a crucial factor influencing the initial onset and severity of the disease and thus the level of alert for achieving good DM control in the early season. The qPCR assay can be used to assess the legacy/inheritance factor and inform early-season disease control. This data could be used to devise an effective strategy for leaf residue and soil management in vineyards.